Synthesizing State-Based Object Systems from LSC Specifications - Harel, David; Kugler, Hillel (International Journal of Foundations of Computer Science, 2002)
Live sequence charts (LSCs) have been defined recently as an extension of message sequence charts (MSCs; or their UML variant, sequence diagrams) for rich inter-object specification. One of the main additions is the notion of universal charts and hot, mandatory behavior, which, among other things, enables one to specify forbidden scenarios. LSCs are thus essentially as expressive as statecharts. This paper deals with synthesis, which is the problem of deciding, given an LSC specification, if there exists a satisfying object system and, if so, to synthesize one automatically. The synthesis problem is crucial in the development of complex systems, since sequence diagrams serve as the manifestation of use cases - whether used formally or informally - and if synthesizable they could lead directly to implementation. Synthesis is considerably harder for LSCs than for MSCs, and we tackle it by defining consistency, showing that an entire LSC specification is consistent iff it is satisfiable by a state-based object system, and then synthesizing a satisfying system as a collection of finite state machines or statecharts. (Also in Proc. 5th Int. Conf. on Implementation and Application of Automata (CIAA 2000), Springer-Verlag, pp. 1–33, Preliminary version appeared as technical report MCS99-20, Weizmann Institute of Science, 1999. )
(Also in Proc. 5th Int. Conf. on Implementation and Application of Automata (CIAA 2000), Springer-Verlag, pp. 1–33, Preliminary version appeared as technical report MCS99-20, Weizmann Institute of Science, 1999. )